Domestic abuse : help for the sufferer - Strickland, Darby A. (Resources for changing lives., 2018)
"Domestic abuse is a heartbreaking and very prevalent issue—and, sadly, it is no stranger to Christian marriages. Though they are filled with both oppressors and oppressed, many churches have little to say on this issue. If you are being oppressed, this can leave you feeling isolated and alone... but you're not alone. Scripture has much to say about your experience, your safety, and God's heart for you—he does not blame you for your suffering and does not tolerate oppression. In fact, he wants to rescue you. Experienced family counselor Darby Strickland helps you to cut through confusion, speak out and find support, and then determine your next steps. God knows the suffering and wounds of oppression, and he delights in redeeming and rescuing—especially his heartbroken children."--